Integrating morphological and molecular approaches for characterizing four species of Dactylogyrus (Monogenea: Dactylogyridae) from Moroccan cyprinids, with comments on their host specificity and phylogenetic relationships - Řehulková,Eva; Rahmouni,Imane; Pariselle,Antoine; Šimková,Andrea (PeerJ, 2021)
Cyprinid fishes are known to harbour highly host-specific gill-associated parasites of Dactylogyrus. High similarity in the morphology of sclerotized structures among Dactylogyrus species, especially those parasitizing congeneric cyprinoids, makes their identification difficult. In this paper, four previously known species of Dactylogyrus are characterized and illustrated under a reliable taxonomic framework integrating morphological and molecular evidence, and their phylogenetic relationships are investigated using molecular data. The species are as follows: D. borjensis from Luciobarbus zayanensis; D. draaensis from Luciobarbus lepineyi; D. ksibii from Luciobarbus ksibi and Luciobarbus rabatensis; and D. marocanus from Carasobarbus fritschii, L. ksibi, L. zayanensis and Pterocapoeta maroccana. Our results revealed intraspecific genetic variability among specimens of D. ksibii collected from two different hosts and geographically distant basins. Phylogenetic reconstruction showed that Dactylogyrus spp. parasitizing Moroccan cyprinids are representatives of three main lineages corresponding to morphological differences and host specificity. Our records of D. marocanus on L. zayanensis and P. maroccana increase the range of available host species i.e.,eight species of four cyprinid genera representing two phylogenetic lineages (i.e., Barbinae and Torinae).
Keywords: Parasite; Monogenea; Dactylogyrus; Cyprinidae; Luciobarbus; Morocco; Phylogeny; Host specificity; DNA; Carasobarbus; Pterocapoeta